Cooperative Guidance & Control of Missiles Autonomous Formation - Wu, Sentang (Springer Nature Singapore : Imprint: Springer, 2019)
This book primarily illustrates the rationale, design and technical realization/verification for the cooperative guidance and control systems (CGCSs) of missile autonomous formation (MAF). From the seven functions to the five major compositions of CGCS, the book systematically explains the theory and modeling, analysis, synthesis and design of CGCSs for MAF, including bionics-based theories. Further, the book addresses how to create corresponding digital simulation analysis systems, as well as hardware in the loop (HIL) simulation test systems and flight test systems, to evaluate the combat effectiveness of MAF. Lastly, it provides detailed information on digital simulation analysis for a large range of wind tunnel test data, as well as test results of HIL system simulations and embedded systems testing.